Partners to Survive: Hoffmannseggia Doellii Root-Associated Microbiome at the Atacama Desert - Maldonado-Soto, J (John Wiley and Sons Inc, 2022)
The discovery and characterization of plant species adapted to extreme environmental conditions have become increasingly important. Hoffmannseggia doellii is a perennial herb endemic to the Chilean Atacama Desert that grows in the western Andes between 2800 and 3600 m above sea level. Its growing habitat is characterized by high radiation and low water and nutrient availability. Under these conditions, H. doellii can grow, reproduce, and develop an edible tuberous root. We characterized the H. doellii soil-associated microbiomes to understand the biotic factors that could influence their surprising ability to survive. We found an increased number of observed species and higher phylogenetic diversity of bacteria and fungi on H. doellii root soils compared with bare soil (BS) along different sites and to soil microbiomes of other plant species. Also, the H. doellii-associated microbiome had a higher incidence of overall positive interactions and fungal within-kingdom interactions than their corresponding BS network. These findings suggest a microbial diversity soil modulation mechanism that may be a characteristic of highly tolerant plants to diverse and extreme environments. Furthermore, since H. doellii is related to important cultivated crops, our results create an opportunity for future studies on climate change adaptation of crop plants. © 2022 The Authors. New Phytologist © 2022 New Phytologist Foundation.